The role of Staphylococcus aureus surface protein SasG in adherence and biofilm formation - FOSTER, TIMOTHY (My University, 2007)
Staphylococcus aureus colonizes the moist squamous epithelium of the anterior nares. One of the adhesins likely to be responsible is the S. aureus surface protein G (SasG), which has sequence similarity with the proteins Pls (plasmin sensitive) of S. aureus and Aap (accumulation associated protein) of Staphylococcus epidermidis. Expression of SasG by a laboratory strain of S. aureus could not be detected by Western immunoblotting. To enable investigation of SasG, the gene was cloned into two expression vectors, the IPTG-inducible pMUTIN4 and the tetracycline-inducible pALC2073, and introduced into S. aureus. Expression of SasG masked the ability of exponentially grown S. aureus cells expressing protein A (Spa), clumping factor B (ClfB) and the fibronectin binding proteins A and B (FnBPA and FnBPB) to bind to IgG, cytokeratin 10 and fibronectin, respectively. SasG also masked binding to fibrinogen mediated by both ClfB and the FnBPs. Western immunoblotting showed no reduction in expression of the blocked adhesins following induction of SasG. SasG size variants with eight, six or five B repeats masked binding to the ligands, whereas variants with four, two or one repeats had no effect. SasG-expressing strains formed peritrichous fibrils (53.47+/-2.51 nm long) of varying density on the cell wall, which were labelled by immunogold negative staining with anti-SasG antibodies. SasG-expressing strains of S. aureus also formed biofilm independently of the polysaccharide intercellular adhesin (PIA). SasG variants with eight, six and five repeats formed biofilm, whereas variants with four, two or one repeats did not. It was concluded that the fibrillar nature of SasG explains its ability to mask binding of S. aureus microbial surface components recognizing adhesive matrix molecules (MSCRAMMs) to their ligands and to promote formation of biofilm. In addition, the strong adhesion of SasG to desquamated nasal epithelial cells likely compensates for its blocking of the binding of S. aureus ClfB to cytokeratin 10, which is important in adhesion to squames by cells lacking SasG. Several clinical isolates expressed SasG at levels similar to those of SH1000 sasG : : pMUTIN4, indicating that the properties described in the laboratory strain SH1000 may be relevant in vivo.
PUBLISHED
PMID: 17660408
Keywords: Microbiology; Staphylococcus aureus